Research of the Influence of Spur Gear Tooth Bilateral Crack on Its Stiffness - Junjie Lai; Yanxue Wang; Chaoyang Jiang (Jixie chuandong)
The time-varying meshing stiffness （TVMS）of gear pair is a major parameter of mechanical dynamics analysis， and its accuracy directly affects the accuracy of dynamics analysis results. At first， the formula for computation of shear stiffness is derived theoretically， and it is applied in the case analysis， the obtained result is compared with and the result of finite element analysis， the result shows that the difference is small. Then， a kind of new crack failure model is established， which is called the gear tooth bilateral asymmetrical crack model. On the basis of the energy method based on the accurate full tooth profile， the calculation formula of TVMS of gear tooth bilateral asymmetrical crack model is derived. Then influence of crack shape on TVMS is analyzed. At last， the analysis validation is carried out by finite element method （FEM）， and the results indicate， the results of finite element method and energy method are basically the same.